THE DESIGN OF KNOWLEDGE MANAGEMENT SYSTEM APPLICATIONS IN THE FORUM OF MGMP TEACHERS AT SMK NETWORK COMPUTER ENGINEERING EXPERTISE - Wulan Andang Purnomo; Fauzi Tri Yuniko; Gunawan Ali (Sean Institute, 2022)
This research discusses the knowledge management information system to improve the skills and professional competence of vocational school teachers in the field of network computer engineering expertise. This research was conducted on the basis that the network computer engineering MGMP forum was not yet optimal in increasing the skills and competence of the vocational school teachers who were members of the MGMP forum. This research is to develop and test the knowledge management system application through validity and practicality tests. The research methodology used is development research with 10 steps of activity. Analysis of the research data shows the knowledge management system application is valid (0.89) and practical (86.98). The results of this study can be concluded that the knowledge management system application that has been developed meets the feasibility of being used.